Analysis of main components of cow weight variation during pregnancy in fetal programming of females (Research, Society and Development, 2021)
The objective of this study was to evaluate the impact of cow's weight variation during gestation on the development and productive characteristics of the carcass and the meat of heifers slaughtered at 18 months of age. Thirty - five cows and their progeny were used. The evaluated treatments were determined according to the matrix weight variation during gestation, expressed as a percentage of the live weight of the matrix at the end of the breeding period. Treatments were: G10, cows that gained from 0.1 to 10.0% of live weight during gestation; P10, cows that lost 0.1 to 10.0% of live weight during gestation; P20, cows that lost from 10.1 to 20.0% of live weight during gestation. Data were analyzed statistically through multivariate analysis and the main components technique. The variables PNAS, PAJDESM, PAJ365, PAJ420, PAJ540, GMD, RCQ, RCF, AOL, GORD, ICC, DIAN, COST, CON, MAT and EGS of heifers were not influenced by maternal performance during gestation. The PCQ, PCF, MUSC, OSSO, TRAS and MARM presented significant correlation with two main components. The G10 treatment presented higher values for PCQ, PCF, TRAS, MUSC and MARM, being located in the I quadrant. Treatment P10 presented a greater amount of OSSO in the carcass, in the IV quadrant. On the other hand, the P20 treatment was located in the II quadrant, presenting the worst values for these variables. The variation in the weight of the cow during pregnancy does not influence the development of the progeny, but it does impact the carcass and meat characteristics.